The tutorial in training of the Nursing future professional - Narciso Águila Rodríguez; Eneida Bravo Polanco; Hilda María Delgado Acosta; Tamara Montenegro Calderón; Lázaro Roberto Herrera Fragoso; Alina Centeno Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Many of the nursing professionals, in their teaching work, should fulfill the function of being a tutor, which goes beyond the framework of the mere knowledge transmission. The figure of the tutor is established as the main axis in the tutorial teaching conception; He has the important mission of training the nurse, which is an honor and a challenge. The mentor must train the future professional in a comprehensively and for it, his highest goal is the formation and production of knowledge, skills, attitudes and values that promote the development of his performance. The objective of this review is to reflect on the function of the nursing tutor, his qualities and challenges in the current times.